SIKAP SISWA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Ramlia; Amirudin Rahim; Haerun Ana (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2025)
This study aims to describe students’ attitudes towards Indonesian language learning in class VIII of SMP Negeri 2 Wadaga, West Muna Regency. A quantitative descriptive method was used with data collected through a structured Likert-scale questionnaire and classroom observations. The questionnaire included four response options: strongly agree, agree, disagree, and strongly disagree. The results revealed that most students expressed a strongly positive attitude toward learning Indonesian. Their responses indicated high enthusiasm for lessons, appreciation for teachers’ teaching methods, and recognition of the relevance of the learning materials to daily life. These findings demonstrate that students’ attitudes are shaped by the teacher’s instructional approach, engaging learning media, and meaningful content. In general, students’ strong agreement reflects a positive emotional and cognitive connection to the subject. The implication of this study is that teachers should maintain and strengthen interactive and contextual learning strategies to foster students’ positive attitudes and motivation toward Indonesian language learning.